PENGARUH LINGKUNGAN KERJA FISIK DAN DUKUNGAN SOSIAL TERHADAP STRES KERJA PADA PERAWAT RUMAH SAKIT ISLAM (RSI) IBNU SINA PAYAKUMBUH - Fitri Rahmadia; Rini Sarianti; Yuki Fitria (Jurnal Ecogen, 2019)
This study aims to prove and analyze the effect of physical work environment and social support on work stress on nurses of the Ibnu Sina Islamic Hospital in Payakumbuh. In this study the population was 103 nurses of the Ibnu Sina Islamic Hospital in Payakumbuh. In this study the sampling method used was total sampling. The analytical method used to prove the hypothesis is to use multiple regression models and t-statistical testing. Based on the results of testing the hypothesis it was found that the first workload had a negative and significant effect on work stress on nurses of the Ibnu Sina Islamic Hospital in Payakumbuh, while the second hypothesis was successfully proven the social support had a negative and significant effect on the work stress of Ibnu Sina Islamic Hospital in Payakumbuh. Keywords: physical work environment and social support on work stress